2009
DOI: 10.1371/journal.pone.0007580
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Stimulates Activity and Alters Behavior in Drosophila melanogaster

Abstract: Circadian rhythms in animals are regulated at the level of individual cells and by systemic signaling to coordinate the activities of multiple tissues. The circadian pacemakers have several physiological outputs, including daily locomotor rhythms. Several redox-active compounds have been found to function in regulation of circadian rhythms in cells, however, how particular compounds might be involved in regulating specific animal behaviors remains largely unknown. Here the effects of hydrogen peroxide on Droso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…Similar findings were recently reported and attributed to increased production of hydrogen peroxide and the consequent alterations in Drosophila activity (Grover et al, 2009). Therefore, it is particularly striking that zinc-deficient SOD1 expression leads to a decrease in physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were recently reported and attributed to increased production of hydrogen peroxide and the consequent alterations in Drosophila activity (Grover et al, 2009). Therefore, it is particularly striking that zinc-deficient SOD1 expression leads to a decrease in physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…For example, one behavioral study on Drosophila has shown that H 2 O 2 causes activity increase and changes in behavior [36]. However, flies fed with H 2 O 2 -containing medium (resulting in fluctuating H 2 O 2 body level) responded differently compared to transgenic flies with increased intrinsic H 2 O 2 production (analogous to the continuous exposure).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that skn-1 regulates the oxidative stress-induced increase in the 20S proteasome in C. elegans, similar to the effect of Nrf2 in mammalian cell cultures. Previous studies have shown that pre-treatment of D. melanogaster with mild doses of oxidants or radiation can result in a subsequent increase in tolerance to oxidative damage (Moskalev et al, 2009 (Grover et al, 2009). For these experiments, flies were collected 0-48h after eclosion.…”
Section: Role Of the 20s Proteasome In H 2 O 2 -Induced Adaptation Inmentioning
confidence: 99%
“…The first step was to develop an appropriately toxic challenge for the flies. Instead of subjecting flies to a single challenge as in mammalian cell culture and C. elegans, the assay employed for D. melanogaster involved incubating the flies in vials containing the toxic dose of H 2 O 2 and scoring survival over time, as previously described (Grover et al, 2009;Sykiotis and Bohmann, 2008;Sykiotis and Bohmann, 2010). Survival was scored every 8h, for up to 104h.…”
Section: Role Of the 20s Proteasome In H 2 O 2 -Induced Adaptation Inmentioning
confidence: 99%